Perceptions of Elementary School Teacher Education Students on the Use of Wordwall Interactive Media as a Quiz - Zeva Adi Fianto; Sekar Purbarini Kawuryan; Bambang Saptono; Mujinem; Galuh Mentari Putri (Jurnal Ilmiah Sekolah Dasar, 2024)
The use of interactive media in learning activities provides new innovations in the world of education. This study aims to analyze the perceptions of PGSD students on the use of Wordwall interactive media as quizzes in elementary school social studies education courses. This research is a quantitative type with 50 PGSD (Elementary School Teacher Education). The research method used in this research is the survey method. Data was collected using a 1-5 Likert scale questionnaire. Questionnaires were distributed to students via the Google form. The data obtained from the study were then analyzed using a Likert scale and the results were converted into a student perception classification table. The results of the analysis of the questionnaire distributed to PGSD students showed that the perceptions of PGSD students regarding the use of Wordwall interactive media as quizzes in elementary school social studies education courses were in the "agree" category. So that future learning can take advantage of Wordwall interactive media. Based on the results of the questionnaire distributed to students, the conclusion that can be drawn is that the use of interactive teaching media such as Wordwall as quizzes can increase students' motivation, learning outcomes, enthusiasm and learning achievements. Because the use of Wordwall interactive media has an attractive appearance, is easy to use and at the end of the quiz work a value rating will appear automatically. So that it can stimulate students to compete to get the maximum value.